Teacher Empowerment: Engaging E-Modules with Book Creators - Elsita Lisnawati Guntar; I Made Agus Oka Gunawan; Ida Ayu Oka Purnami (Universitas Pendidikan Ganesha, 2024)
Technological advances offer great opportunities to enrich the learning process, one of which is through the development of e-modules. However, the use of this technology is often not optimal due to limited training or lack of collaboration between teachers and book creators as content experts. By involving book creators, teachers can get guidance in producing teaching materials that are not only technology-based, but also have high quality standards. This research aims to increase teacher competence in creating interactive learning e-modules using the Book Creator application in one of the state schools. Through training and mentoring, teachers of all subjects are trained to design interesting and effective modules. In this research, researchers used field note instruments, questionnaires and unstructured interviews to find out the problems faced by participants. The number of participants was 48 people, participants came from teachers in various fields of expertise. The evaluation results show that this training is very effective in increasing participants' understanding and skills in making digital books. As many as 69.4% of participants strongly agreed that they felt more helped by using the Book Creator-based E-Module, while 72.2% felt significant benefits from this training. The resulting modules were then implemented in classroom learning and succeeded in increasing students' motivation and understanding of the subject. This shows that training in creating e-modules based on Book Creator can be an effective solution for improving the quality of learning in schools. The implications of this research provide a significant contribution to teacher professional development, especially in the context of the use of technology and enrichment of teaching materials.